PENGARUH KOTORAN AYAM DAN MIKORIZA Glomus aggregatum TERHADAP PERTUMBUHAN KEDELAI (Glycine max) PADA TANAH GAMBUT - Iqbal, Muhamad; Linda, Riza; Mukarlina, Mukarlina (Jurnal Protobiont, 2020)
Peat soil in West Kalimantan has been contained low of nutrient level so it affects the growth of soybeans. One effort to increase the availability of nutrients in peat soils is by using mycorrhiza and chicken manure fertilizer. This research aims to determine the growth of soybeans by administering chicken manure and mycorrhiza on peat soils. The research was conducted from January to April 2019. The research design used was a Completely Randomized Design Factorial consisting of 2 factors with 4 replications. The first factor is mycorrhiza fungi: M1 (0 gr/polybag), M2 (5 gr/polybag), M3 (10 gr/polybag), M4 (15 gr/polybag) and the second factor is chicken manure fertilizer: P1 (0 tons/ha) , P2 (5 tons/ha), P3 (10 tons/ha), P4 (15 tons/ha). The results showed that the single chicken manure application significantly affected all observed parameters with 15 tons/ha chicken manure fertilizer. Mycorrhiza fungi just a significantly effect on fresh weight and dry weight. Also, the combination of mycorrhiza fungi and chicken manure fertilizer just a significantly affected wet weight and dry weight with combination 5 g mycorrhiza and 5 tons/ha of chicken manure fertilizer.